121 Violence against older adults: perpetrators and mechanisms of geriatric physical assault injuries treated in us emergency departments, 2006–2014. (19th September 2017) - Rosen, Tony; Lachs, David; Clark, Sunday; Bloemen, Elizabeth; Udow, Erica; Varki, Veena; Yonashiro-Cho, Jeanine
Abstract : Purpose: Older adults are common victims of assault, many of which may result in severe injuries. Yet, circumstances surrounding assaults in this population haven't been well-described. This study examines perpetrators and mechanisms of geriatric physical assault injuries treated at US Emergency Departments (EDs). Methods: We conducted an analysis of assault injuries in patients aged ¥60 treated in EDs during 2006–2014 using the National Electronic Injury Surveillance System-All Injury Program, which collects data from a nationally representative stratified probability sample of US hospitals and includes a brief narrative about injury circumstances for each case. We examined narratives based on a pre-determined protocol. Results: From 2006–2014, 7761 assault injury-related ED visits occurred in victims aged â‰¥60, representing an estimated 4 25 992 treated in U.S. EDs. 62% of assault victims were male. Victims had a mean age of 68. Perpetrator information was available for 53.3% of cases, mechanism information for 66.7%, and weapon information for 58.7%. The most common perpetrators were family (28.8% of cases with information) and strangers/robbers (27.7%). 57.6% of perpetrators were in a relationship with an expectation of trust with the victim, suggesting that assaults were physical elder abuse. The most common mechanisms of injury were beating with fists (31.6% of cases with information), striking with objects (27.3%), and fall during altercation (20.2%). Multiple mechanisms were present in 33.3%. Assailants most frequently used their body parts as weapons (75.8% of cases with information), with fists (32.4%) most common. 37.8% used objects, most frequently gun (4.8% shot and 2.4% used as blunt object) or knife (4.9%). Conclusion: Our findings provide ideas about circumstances surrounding geriatric assault injuries. The majority of geriatric assault victims were suffering from physical elder abuse. Most perpetrators struck victims and used personal weapons. Further research is needed to better understand these assaults to develop prevention strategies.